How scarcity of certainty affects your cognitive functioning - Agne Kajackaite (WZB Berlin Social Science Center, 2020)
Beyond the many choices and challenges humans face during the pandemic lies a constant cognitive trade-off: Those who excessively absorb news against uncertainty run the risk of impaired cognitive functions.
Keywords: 300; cognition; cognitive ability; concentration; contagious disease; Coronavirus; COVID-19; epidemic; security